Examining Purchase Behavior of Electric Vehicles as an Effort to Reduce Air Pollution: Theory of Planned Behavior - Amelindha Vania; Ardiansyah Muhammad (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Central Jakarta has increasingly bad levels of air pollution, it is recorded that Jakarta is ranked third with the worst air in the world. Purchasing an electric vehicle is one way to minimize bad air. This research uses the Theory of Planned Behavior (TPB) to understand and predict what characteristics or variables influence the purchase of electric vehicles in Central Jakarta. The research sample consisted of 166 respondents who had purchased an electric vehicle. Data analysis used descriptive statistics and PLS-SEM. The perception of ease of avoiding pollution influences the lack of desire to protect oneself, and the protect intention (PI) influences purchasing behavior (PB). Subjective norms (SN) and attitudes towards electric vehicle purchasing behavior (ATB) are important elements that can increase a person's desire to defend against pollution by purchasing an electric vehicle. Perceived behavioral control (PBC) challenges subjective norms and attitudes toward electric vehicle purchasing behavior. Perceived behavioral control is proven to be a solution to preventing air pollution.